A new Tardigrade species, Stygarctus keralensis sp. nov. (Arthrotardigrada: Stygarctidae) from the intertidal zone of Southwest coast of India - Vishnudattan, N. K.; Nandan, S. Bijoy; Hansen, J. G.; Jayachandran, P. R. (Zootaxa, 2021)
Stygarctus keralensis sp. nov. (Arthrotardigrada: Stygarctidae), is described from the intertidal sandy sediments of Vadakara beach, Kerala, Southwest coast of India. To a certain extent, this new species shows morphological similarity with Stygarctus gourbaultae Renaud-Mornant, 1981, however it can be differentiated by some significant distinguishable characters like double looped seminal receptacle ducts and the presence of a bow shaped internal thickening in between the opening of seminal receptacles situated below the level of gonopore and above the anus; unsculptured body plates I-III; paired sub-cephalic pore/muscle attachment; shape and structure of caudal processes. Presence of minute spikes on third lateral processes in the new species is another unique character by which it can be easily differentiated from S. gourbaultae.